Human Rights Protection Related to Arrest, Detention, and Judicial Remedies: A Comparative Legal Study of Indonesia, Saudi Arabia, and Egypt - Sahat Maruli Tua Situmeang; Athari Farhani; Subagyo Sri Utomo (Lex Scientia Law Review, 2026)
Arrest, detention, and pretrial legal remedies constitute crucial stages in criminal procedure because they determine the extent to which state coercive power is constrained by due process and human rights guarantees. This study aims to examine and compare the legal regulation and practical implementation of arrest, detention, and pretrial review mechanisms in Indonesia, Saudi Arabia, and Egypt, with particular attention to their compliance with human rights standards. Methodologically, this research employs normative legal research using a doctrinal and institutional comparative approach, analyzing statutory provisions, procedural regulations, constitutional safeguards, and relevant reports and legal materials. The findings show that Indonesia provides relatively stronger procedural safeguards through the Criminal Procedure Code (KUHAP) and the praperadilan mechanism, which functions as judicial control over unlawful arrest and detention. Egypt formally recognizes legal oversight through the public prosecution and judicial review, yet persistent implementation gaps raise concerns regarding prolonged pretrial detention and limited procedural transparency. In contrast, Saudi Arabia demonstrates weaker independent judicial supervision at the pretrial stage, increasing the risk of arbitrary detention and executive overreach. This comparative analysis concludes that strengthening effective judicial review, access to legal counsel, and procedural accountability is essential to prevent abuses of power. The study recommends reinforcing institutional checks on detention practices to ensure greater alignment with international human rights principles and due process requirements.